Dekonstruksi Kapitalisasi Dalam Komunikasi Digital Generasi Z - S, Sugiarti; Nurfaonah, Endang; Hasanah, Uswatun (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Language is the primary communication tool in daily life, also serving as a symbol of national identity and a custodian of culture. In Indonesia, the use of the Indonesian language is standardized through the General Guidelines for Indonesian Spelling (PUEBI), including capitalization rules. However, in the digital era, especially among Generation Z, there has been a shift in language practices due to the influence of social media. One prominent phenomenon is the trend of